2009
DOI: 10.3724/sp.j.1005.2008.01477
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of plant height and ear position in maize (<I>Zea mays</I> L.)

Abstract: A molecular linkage map for the maize hybrid of cross between Ye478 and Dan340 was constructed by using 150 co-dominant SSR markers. The total map length was 1 478.7 cM with an average interval of 10.0 cM. Composite interval mapping was used to identify the plant height (PH) and ear position (EH) QTL at 5 environments based on the phenotypic data of 397 F2:3 families. Then 21 PH and 25 EH relevant QTL were identified. The mean contribution of 12.2% and 14.9% QTL for plant height was identified at the interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
5
15
2
Order By: Relevance
“…The missing proportion of the genotypes was 6.1%. The distribution of these SSR markers was consistent with publicly available published linkage maps (Lima et al, 2006;Frascaroli et al, 2007;Yang et al, 2008) and the integrated map in the maize genome database (www.maizegdb.org). …”
supporting
confidence: 57%
“…The missing proportion of the genotypes was 6.1%. The distribution of these SSR markers was consistent with publicly available published linkage maps (Lima et al, 2006;Frascaroli et al, 2007;Yang et al, 2008) and the integrated map in the maize genome database (www.maizegdb.org). …”
supporting
confidence: 57%
“…But, different parental lines probably provide different results in QTL number, position or effect. For example, Zhang et al identified nine QTLs for plant height using the two parents R15 and 478, with two, one, four, one and one on chromosomes 2, 3, 4, 8 and 9, respectively [7]; while in the report by Yang et al, Ye478 and Dan340 were used as parental lines, and twenty-one QTLs for plant height were identified on chromosomes on 1(seven), 2 (three), 3 (three), 5 (three), 7 (two), 8 (one) and 10 (two) [8]. Additionally, previous segregation populations used to detect the QTL for maize plant height were focused on temporal F 2 [9,10], while recombinant inbred line (RIL) population possessing the merit immortality were seldom applied [11].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies that aimed to identify QTL for ear height in maize (Zhang et al, 2006a;Yang et al, 2008;Bai et al, 2010), and some QTL were located on different chromosomes of maize. Compared to previous studies, our results were different in terms of QTL number, location, and genetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many studies on the QTL that affect agronomic traits in maize, such as yield (Coque and Gallais, 2006;Ribaut et al, 2007), florescence (Szalma et al, 2007;Liu et al, 2010), and plant morphology (Ku et al, 2010). With respect to the ear height trait, some QTL were also identified from published reports (Kraja and Dudley, 2000;Flint-Garcia et al, 2003;Lima et al, 2006;Yang et al, 2008). Nevertheless, different studies provided different results, including QTL number, distribution, and genetic effect.…”
Section: Introductionmentioning
confidence: 99%